A sala de aula de filosofia como espaço de vivências transformadoras: interculturalidade e amorosidade na formação docente - Carvalho, Elvio de (2016)
He theme of this research is focused on the training of professor of philosophy based on the same aspects of intercultural and loveliness. For the teacher can develop an emancipatory pedagogical practice teacher / pupil in exchange for meaningful experiences. Investigative space is determined as the classroom context of a Public School in the city of Rosário do Sul - RS. In this sense, we noted the need to reflect on the action of Philosophy teacher making it necessary to an understanding about the knowledge and practices that the academy is providing this professional education. Given these considerations point out as significant element the limitations of a pedagogical practice that ignores the culture and life experiences of the student, since for the construction of knowledge the desire for learning is required. Thus, affective relationship is a prerequisite for a personal and social emancipation of the subject. The affection in this research context is perceived as a broader meaning, referring to the experiences of individuals and forms of more complex and essentially human expression. .In Addition, we understand that the teacher needs to develop a critical approach to help build a school from the real, the significant and love. For this, we point out that emancipation is grounded in the knowledge and the teacher do in the relations of affection, respect and recognition as possibilities to rebuild and reinvent the history and knowledge as a fundamental part of freedom.